Action Prediction Allows Hypothesis Testing via Internal Forward Models at 6 Months of Age - Gredebäck, Gustaf; Lindskog, Marcus; Juvrud, Joshua C.; Green, Dorota; Marciszko, Carin (Frontiers in Psychology, 2018)
We propose that action prediction provides a cornerstone in a learning process known as internal forward models. According to this suggestion infants predictions (looking to the mouth of someone moving a spoon upwards) will moments later be validated or proven false (spoon was in fact directed towards a bowl), information that is directly perceived as the distance between the predicted and actual goal. Using an individual difference approach we demonstrate that action prediction correlate with the tendency to react with surprise when social interactions are not acted out as expected. This association is demonstrated across tasks and in a large sample (n=118) at 6 months of age. In addition, action prediction, but not action evaluation, correlates with the infants own motor performance at the same age, replicating previously findings. These results provide the first indication that infants might rely on internal forward models to structure the social world.